Mapping the phonological processes of 4, 5, and 6 years old children in PAUD Tasikmalaya - Pratiwi, Anggia Suci; Wijana, I Dewa Putu; Sutrisno, Adi; Nurfitriani, Meiliana (BAHASTRA, 2025)
Phonological ability reflects the perceptual and cognitive mechanisms required for children to learn and produce speech. This study aims to map phonological processes in early childhood at PAUD institutions in Tasikmalaya. Using a qualitative descriptive approach, data were collected from 315 children aged 4–6 years (77 aged 4, 148 aged 5, and 90 aged 6) across five schools: RA Baiturrahman, TK Negeri Pembina, TK Cangkurileung Kartika IX-10, TK IT Ihya As-Sunah, and Joykids. Speech samples in Indonesian were obtained through recordings of both structured and conversational speech. Data validity was ensured through expert judgment, and analysis followed the stages of data reduction, display, and verification. Results show that assimilation was the most dominant phonological process for both vowels and consonants across all ages. For vowels, assimilation declined with age (9 cases at age 4, 7 at age 5, and 3 at age 6), while addition (4 → 2 → 2) and substitution (3 → 0 → 1) were less frequent. Consonant assimilation was more prevalent (62 → 71 → 27), with gliding substitution (13 → 5 → 0) and general substitution (4 → 2 → 0) steadily decreasing. Sound addition appeared only at age 6 (3 cases). These findings indicate that vowel mastery stabilizes earlier, while consonant mastery involves more complex developmental processes. The study provides baseline data for identifying phonological difficulties early and offers guidance for PAUD teachers to recognize ongoing phonological processes beyond age six as possible signs of language delay.